Sistematika penulisan kitab at-thabaqat al-kubra karya ibnu sa’ad - aminulloh, rohim (Maliki Interdisciplinary Journal, 2025)
This article analyzes Ibn Sa'd's At-Thabaqat al-Kubra, a monumental work that uniquely integrates hadith scholarship with Islamic historiography. More than a collection of biographies, At-Thabaqat al-Kubra is a comprehensive study of the development of Muslims from the prophetic period to the generation of the tabi'in. The concept of thabaqat, a grouping of figures based on generation and hadith transmission, is a key method in this work to assess the authenticity and strength of the sanad. Ibn Sa'd, the foremost historian and hadith scholar of the ninth century CE, shows great care and precision in collecting and verifying information, giving priority to primary sources and cross-verification. The work not only records the biographies of important figures but also provides a rich social and political historical context. The structure of At-Thabaqat al-Kubra, organized by thabaqat, makes it easy to understand the development of Islam and the relationships between generations. Moreover, it provides a comprehensive overview of the role of women in Islamic history. At-Thabaqat al-Kubra has become a major source for the study of hadith and Islamic history, demonstrating the importance of thabaqat as a method of preserving the authenticity of narrations and providing a deep and accurate understanding of history.